Belowground performance of novel short-stature maize under varying nitrogen rates across contrasting soil types - Binod Joshi; Raziel A. Ordóñez; Daniel Quinn; Chad Penn; Carson Pearl; Tony J. Vyn; Yichao Rui (Field Crops Research, 2026)

Impacts of hybrid selection and nitrogen fertilization on root-derived carbon inputs in maize - Carson Pearl; Raziel A. Ordóñez; Cindy Prescott; Daniel Quinn; Roland Wilhelm; Chad Penn; Binod Joshi; Yichao Rui (Plant and Soil, 2026)
Background and Aims Root-derived carbon (C) inputs are increasingly recognized as important precursors to soil organic carbon (SOC). However, the extent to which these inputs can be influenced by nitrogen (N) fertilizer management and plant stature remains poorly understood. This study investigated how N fertilization rate and maize hybrid stature trade off between above- and belowground performance, including investment in root traits, exudation, and soil microbial C pools. Methods Tall- and short-stature maize (Zea mays) hybrids, from Bayer’s breeding pipeline, were grown in a pot experiment in two soil matrices (sandy and loamy), with N fertilization rates of 0, 90, 180, and 270 kg N ha⁻ 1 . C pools in above- and belowground compartments were assessed, including root exudates, root biomass and length, soil microbial biomass C, and total soil C. Results Soil matrix and maize hybrids of different stature primarily explained differences in root exudation and belowground C inputs. Short-stature maize produced 22% greater dry root biomass than tall maize across N treatments. Loamy soils accumulated higher soil microbial biomass C and peaked at intermediate N rates, where fertilization achieved the greatest response in root biomass and C inputs. The highest N rates resulted in lower belowground C investment (particularly > 180 kg N ha⁻ 1 in loamy soil). Conclusion Maize hybrid selection and N fertilization interaction influenced root-derived C inputs and soil microbial biomass, with short-stature hybrids and moderate N rates enhancing belowground C allocation. These findings suggest that short-stature maize and avoiding excessive N fertilizer rates can enhance root contributions to key soil C pools.

Nitrogen addition and rhizosphere effects differentially shape prokaryotic and fungal communities in peanut–maize cropping systems - Yang Chen; Zejin Zhang; Yichao Rui; Carson Pearl; Sheng Lu; Fang Wang; Flemming Ekelund; Yanbin Hao; Xiaoyong Cui (Rhizosphere, 2025)